Study on Calculation Method of Soluble Aerosol Removal Efficiency Under High Humidity Condition - Li, Yingzhi; Ma, Qianchao; Sun, Zhongning; Gu, Haifeng; Zhou, Yanmin; Shi, Kaiyi (Frontiers in Energy Research, 2019)
Pool scrubbing is a potential method to removal aerosol under accident conditions of the nuclear power plants. The relative humidity of aerosol laden gas will increase when it passes through the liquid pool, which cause the hygroscopic growth of soluble aerosol. The hygroscopic growth of soluble aerosol can lead to the deviation of the size distribution of aerosol at the outlet of the liquid pool, resulting in a large error of the removal efficiency calculation results. In order to solve this problem, the size distribution of sodium chloride before and after penetrating the liquid phase was experimentally measured at gas flow rate of 4lpm and liquid height of 80 cm. Two methods of calculating the removal efficiency were proposed and compared. One method is directly calculating the removal efficiency by adding a diffusion drying tube before the aerosol laden gas enters the SMPS to reduce the relative humidity of sample gas below efflorescence point. Another method is modifying the aerosol size distribution and concentration curve by using the hygroscopic growth theory of soluble aerosols. The experiment results obtained by the two methods are in good agreement with the relative error within 20%.